Social protection in Bangladesh : building effective social safety nets and ladders out of poverty - Rahman, Hossain Zillur, 1951-; United Nations Development Programme (Dhaka: Univ. Press Limited, 2014)
Contributed articles.
"United Nations Development Programme."
Includes bibliographical references and index.
Rasal
Keywords: Economic assistance, Domestic -- Bangladesh; Poor -- Bangladesh; Bangladesh -- Economic policy